2014
DOI: 10.1161/circep.113.000899
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the First and Second Cryoballoon

Abstract: There were 2 main objectives:1. To compare the procedural efficacy of CBG1 and CBG2 by analyzing rates of acute PVI, time to isolation (TTI), balloon © 2014 American Heart Association, Inc. Original ArticleBackground-Cryoballoon (CB) ablation results in >70% freedom from atrial fibrillation at 1 year. Single-center data of the first (CBG1) and second (CBG2) cryoballoon, recently introduced, were analyzed to compare safety and efficacy. Methods and Results-From March 2011 to December 2012, CB ablation with spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…3 In studies using CB2, the PNP rate has ranged from 3.5% to 27.5% and the vast majority of cases regressed completely. [12][13][14][15][16][17] The rate of threatened PNP in our previous series using CB1 1 was identical to the 1 observed in this series with CB2: 12% versus 13.6%, respectively. This similarity occurred despite more frequent use of 28-mm CB2 (90% versus 32%).…”
Section: Discussionsupporting
confidence: 78%
“…3 In studies using CB2, the PNP rate has ranged from 3.5% to 27.5% and the vast majority of cases regressed completely. [12][13][14][15][16][17] The rate of threatened PNP in our previous series using CB1 1 was identical to the 1 observed in this series with CB2: 12% versus 13.6%, respectively. This similarity occurred despite more frequent use of 28-mm CB2 (90% versus 32%).…”
Section: Discussionsupporting
confidence: 78%
“…2-10 It has a single procedure one-year success rate in paroxysmal AF of >80 % in patients no longer taking antiarrhythmic drugs. [2][3][4][5][6][7][8][9][10] A large multicentre ablation registry study from Germany showed that the overall rates of major complications were similar in cryoablation and RF. 11 We compared the results of 3,000 RF and balloon PVI procedures for AF and found a significantly reduced risk of cardiac tamponade in balloon ablation; no cardiac tamponade was observed in the cryoablation group.…”
mentioning
confidence: 99%
“…7 The more recently introduced second-generation CB has exhibited a significantly higher performance than the first-generation CB because of the improved cooling effect. 8,9 However, CB ablation cannot specifically control the left atrial (LA) lesion size, which means that the isolation area is basically defined by the LA and PV anatomy. Although a previous study showed that the isolation area was wide and antral during the acute phase post 28-mm secondgeneration CB ablation, [10][11][12] the data during the chronic phase (after disappearance of tissue edema) has not been reported.…”
mentioning
confidence: 99%